Composition of electron temperature gradient driven plasma turbulence in JET-ILW tokamak plasmas - B. Chapman-Oplopoiou; J. Walker; D. R. Hatch; T. Görler; JET contributors (Physical Review Research)
This letter reports on new fundamental insights into small scale plasma turbulence that is responsible for confinement degradation on the JET tokamak. We compare the structure of electron temperature gradient (ETG) driven turbulence in the edge region of two JET ITER-like-wall (ILW) high-confinement-mode discharges operating at different levels of gas fuelling. By artificially removing the toroidal drifts from our gyrokinetic turbulence simulations, we demonstrate that the high gas pulse has a substantial component from the toroidal branch of ETG turbulence whilst the low gas pulse is completely driven by slab ETG turbulence. This enables us to explicitly answer why increased gas puffing on JET-ILW leads to confinement degradation.